2012
DOI: 10.1007/s10562-012-0785-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Improved Photocatalytic Activity of WO3·0.33H2O Nanonetworks

Abstract: Multi-structural tungsten oxide (WO 3 Á0.33H 2 O) samples were prepared using a hydrothermal method in the presence of different salts Na 2 SO 4 and CaCl 2 respectively. The experimental results showed that pH value of the reaction solution greatly affects crystal morphology of the final products. To explore the photocatalysis originated from nanonetwork hierarchical structure, the photodegradation of methylene blue was carried out under simulated sunlight irradiation. The photocatalytic activity of the WO 3 Á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In this way, 0D (dots), 1D (rods, whiskers, and fibres), 2D (plates, films), or 3D (large particles, blocks) WO 3 materials can be synthesized. Various types of nanostructured tungsten oxide have been reported, from simple, spherical nanoparticles [34] to WO 3 -based aerogel networks [35], quantum dots [36][37][38][39], nanostructured films [40] (including nanoplate films [41], nanorod films [42], honeycomb-structured films [43], and mesoporous films [44]), nanobelts [45], nanofibres [46], nanowires [30,46,47], bundle-like nanowires [30,48], nanonetworks [49], hollow spheres [50], macroporous spheres [51], wedge-like architectures [52], nanorods [53,54], nanocuboids [34], square nanoplates [55], nanosheets [56], nanoleaves [57], and urchin-like [30,58], flower-like [59][60][61], and tree-like nanostructures [62,63], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, 0D (dots), 1D (rods, whiskers, and fibres), 2D (plates, films), or 3D (large particles, blocks) WO 3 materials can be synthesized. Various types of nanostructured tungsten oxide have been reported, from simple, spherical nanoparticles [34] to WO 3 -based aerogel networks [35], quantum dots [36][37][38][39], nanostructured films [40] (including nanoplate films [41], nanorod films [42], honeycomb-structured films [43], and mesoporous films [44]), nanobelts [45], nanofibres [46], nanowires [30,46,47], bundle-like nanowires [30,48], nanonetworks [49], hollow spheres [50], macroporous spheres [51], wedge-like architectures [52], nanorods [53,54], nanocuboids [34], square nanoplates [55], nanosheets [56], nanoleaves [57], and urchin-like [30,58], flower-like [59][60][61], and tree-like nanostructures [62,63], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The nanorod formation probably proceeds through oriented attachment that is accompanied by the stacking and organization of primary nuclei via dipole-dipole interactions. The aggregation of nanorod lead to plate-like [71] or self-assembly of these nanorods through hydrogen bonding forms snowflake-like morphology [73]. The self-assembly is a thermodynamic process driven by the principle of energy minimization and the self assembled aggregates will be in equilibrium [73,76,79].…”
mentioning
confidence: 99%
“…In particular, composition and crystal structure are also important and directly influential factors. 19,[22][23][24][25][26] For example, Yu et al studied the photocatalytic properties of orthorhombic WO 3 ÁH 2 O and monoclinic WO 3 , where WO 3 ÁH 2 O has enhanced an photocatalytic property compared to WO 3 . 23 Shi et al reported the photodegradation of methylene blue over hexagonal WO 3 , orthorhombic WO 3 Á0.33H 2 O, and cubic WO 3 Á0.5H 2 O, wherein WO 3 Á0.5H 2 O displays the best performance.…”
Section: Introductionmentioning
confidence: 99%